Love in the Time of Diaspora. Global Markets and Local Meanings in Prostitution, Marriage and Womanhood in Cuba. - Kummels, Ingrid (Madrid ES: Iberoamericana Editorial)
Relaciona el fenómeno de la globalización con el problema de la prostitución en Cuba.
Keywords: CUBA; GLOBALIZACION; PROSTITUCIÓN